Sleep tracking in The Female Co. across off-season/pre-season - Plumb, M.; Cook-Black, L. (Journal of Science and Medicine in Sport, 2024)
Introduction: The Female Co. a not-for-profit company, is committed to bridging the significant disparities in access to sporting and educational opportunities for women and girls in the North, particularly in Cairns and its surrounding areas. The trail program offered a multi-faceted approach to athlete development, which included: athlete screening and performance testing; sleep health, 12-week strength and conditioning program; educational sessions; recovery and injury prevention; goal setting and session tracking, various questionnaires on mental health and well-being, and mentorship from professional female athletes. Working with primarily emerging female athletes we aimed to investigate the quality, quantity and timing of sleep in The Female Co. athletes during off-season/pre-season (Dec 2023 - March 2024) to gain insight into baseline sleep behaviors. Methods: Twelve female athletes mean age 22years (range 15 - 32 years), five netball, four rugby league, one basketball, one AFL and one football. From a representative level three competed internationally, one national, two state, and six regional. The Pittsburgh Sleep Quality Index (PSQI) is a self-report measure of sleep quality, consisting of 19 items grouped into seven component scores, which are equally weighted. Global scores > 5 are generally indicate poor sleep quality. The Morningness- Eveningness Questionnaire (MEQ-SA) consists of 19 items to assess individual differences in morningness and eveningness, providing a global score which is used to categorize chronotype. Data derived from sleep diaries and GT9X wrist activity monitors (s (ActiGraph Corp, Pensacola, FL, USA) were used to determine duration and quality of sleep obtained. The sleep-related dependent variables were bedtime, wake-up time, sleep onset latency (SOL), time in bed (TIB), total sleep time (TST), sleep efficiency (SE), and wake after sleep onset (WASO). Results: Global PSQI indicated 75% of female athletes identifying as poor sleepers (range 2 - 14). Total sleep mean 7hrs (range 3.0 - 10.00hrs). Sleep latency mean 30mins (range 5 - 90mins). Sleep quality 12.5% very good, 62.5% fairly good, 12.5% fairly bad, and 12.5% very bad. Sleep disturbance 50% once or twice a week and 50% less than once a week. The MEQ-SA indicated 71% of female athletes were neither type and 29% moderately morning type. Actigraph group data indicated SE (mean 75%), TIB (mean 536.8mins), TST (mean 397.4mins), WASO (mean 128.2mins), number of awakenings (mean 33), average awakening time (mean 3.7mins), and SOL (11.2min). Discussion: The findings show the emerging female athletes are achieving < 7hrs sleep during off/pre-season, sleep efficiency is 75% (normal = 80%) and wake after sleep onset is exceptionally high at 28% (normal = 10%) at 28%, suggesting sleep behavior metrics are sub-optimal in this group Impact/Application to the field: Maximizing recovery and sleep across the off/pre-season need to be addressed with individualized sleep hygiene education sessions targeted to establish regular bed and wake times and to increase sleep duration and decrease sleep disturbances. Future work will explore sleep during season as it is hypothesized sleep metrics will be more deficient, as many of our athletes travel inter-state for games and trails, and further afield for competition. Declaration: My co-authors and I acknowledge that we have no conflict of interest of relevance to the submission of this abstract.